Biomassa de raízes em ilhas de mata de savanas de Roraima: efeito da dimensão do fragmento, distribuição espacial e variáveis edáficas - Turcios, Maryory Medina (2015)
Root biomass in forest ecosystems scattered in Amazonian savanna matrix is poorly studied and indirectly calculated within the National Inventory of carbon sources and reservoirs in Brazil. The goal of the study is to estimate root biomass in forest islands dispersed in Roraima savanna taking into account the size effect of these forest fragments, spatial distribution (edge and interior) and edaphic variables as biomass sources of variation. Sampling was conducted in 12 different forest islands by size categories (small ≤10 ha, medium = 10-20 ha, large = 20-60 ha) and the edge and the forest interior. Soil samples (1 m deep) were performed at equal distances along transects established in the north - south direction on each forest island. All root diameter ≥ 2 mm were manually screened at intervals of 10 cm in the soil vertical column and converted in mass per unit area. Chemical and physical soil analyzes were made in each10 cm interval. Data analysis was performed using ANOVA, t test and linear regression. The average root biomass did not differ in the size of fragments, resulting in 38.8 ± 22.4 t ha-1 as the overall mean for all fragments. However the edge mean (37.6 ± 19.6 t ha-1) was distinct from the interior (23.3 ± 24.4 t ha-1), regardless of the size of the islands, suggesting that it is affected by floristic and structural distinctions between the edge and the interior. Only 50% of the variation in root biomass along the vertical profile (0-1 m) were explained by the soil characteristics due to chemical and physical uniformity of the sampled soils. The highest concentration of roots was recorded between 0-30 cm (fine = 32.8%, medium = 55.9% and coarse = 11.3%), with no differences between the sizes of the fragments in this depth range. The ratio root: shoot in the sampled forest islands was 0.40 ± 0.28 (0-1 m deep). The conclusion is that root biomass in forest fragments dispersed in Roraima savannah is not affected by the size of the fragments, but is distinct between edge and interior of the islands, which can be partially explained by differences in the structure and floristic composition between edge and interior.